“A Study To Assess The Knowledge And Practice Of Medication Safety Among Staff Nurses In Selected Hospital At Mangaluru'' (Journal of Pharmaceutical Negative Results, 2023)
Objectives: To assess the knowledge of medication safety among staff nurses, to assess the practice on medication safety among staff nurses, to find out the correlation between knowledge and practice of medication safety among staff nurses and to find the association of knowledge and practice of medication safety among staff nurses with selected demographic variables.Method: Descriptive research design was carried out on 94 staff nurses working in selected hospital, selected by non-probability purposive sampling technique to test the knowledge and practice on medication safety. The data was collected by using structured knowledge questionnaire and self-observational checklist.Results: The study revealed that majority (89.4%) of the subjects belongs to an age group of 20-29 years and majorities (90.4%) of them were female. Most (45.7%) of the subjects belongs to B.Sc nursing educational status and majority (59.6%) of the subjects had the clinical experience of less than 2 years. Most of (57.4%) of the subjects were working in general ward and majorities (75.5%) of the subjects were undergone training on medication safety. The study showed that 81.9% of the subjects had adequate, 14.9% of the subjects had moderate and 3.2% of the subjects had poor knowledge regarding medication safety. The study revealed that 60.6% of the subjects had adequate and 39.3% of the subjects had moderate level of practice of medication safety. There was a significant positive correlation between knowledge and practice of medication safety (p=0.002, p<0.05). Hence H1 was accepted. There was a significant association with knowledge on medication safety and selected demographic variables such as age in years (ꭓ2=3.059, p<0.05), gender (ꭓ2=0.724, p<0.05), educational status (ꭓ2=23.658, p<0.05), clinical experience in years (ꭓ2=5.32, p<0.05), area of working (ꭓ2=23.738, p<0.05) and undergone any training on medication safety (ꭓ2=1.007, p<0.05). Hence H2 also accepted.Conclusion: Most of the staff nurses got adequate knowledge and practice on medication safety. Only few of the staff nurses with poor knowledge and moderate practice which can be improved by providing in-service education.